Students’ Perception on Business in Digital Era - Ni Luh Putu Uttari Premananda; Md. Yudyantara Risadi (Fakultas Dharma Duta UHN IGB Sugriwa Denpasar, 2023)
This research aimed to analyze the students’ perception on doinf business in digital era. The objectives of the research were (1) to investigate students’ perceptionof using E-commerce in digital era, (2) to figure out the implications of E-commercein students’ daily life. This research was conducted online for students of university inBali. The data was collected from the questionnaire through google form and wasshared online. the result of the study showed that the quantitative data revealed thatparticipants had positive perceptions toward E-Commerce (TikTok shop, Shopee,Tokopedia, etc) in doing business in digital era. For instance, most of them agree thatE-commerce is beneficial tool for buying dan selling items and even delivering goods,majority of participants agree that they can find the desired items with ease. Thesefinding suggested that students can use E-commerce for doing business in digital eraand they are able to learn new things regarding to business with E-commerce in digitalera.